Nonadiabatic photodissociation dynamics of indole using multi-configuration time-dependent Hartree method - Ray, Soumyadip; Sasmal, Sudip; Mondal, Padmabati (The journal of chemical physics, 2025)
Indole, being a biologically relevant and abundant chromophore, is a prime molecule of interest in both experimental and computational research. In the current work, the N-H photodissociation dynamics of indole have been studied using nonadiabatic quantum dynamics. Potential energy cuts (PECs) along important vibrational modes have been calculated using the multi-state complete active space self-consistent field method with (10,9) active space. The important vibrational modes for the whole process were detected based on symmetry analysis and the strength of the vibronic couplings. The multi-mode multi-state model vibronic Hamiltonian is constructed by the parameters obtained from the fitting of ab initio PECs, including Morse and harmonic functions and vibronic couplings. The nonadiabatic quantum dynamics is performed using a four state multimode Hamiltonian with the multi-configuration time-dependent Hartree method. For the N-H stretching, Q42 turns out to be the most important among all normal modes. The third excited diabatic state shows an anharmonic, dissociative π-σ* character along Q42. The non-adiabatic coupling strength between the La and π-σ* plays a crucial role in controlling the photodissociation. The out-of-plane C-N-H bending, despite being directly related to the N-H group, is found to have a negligible contribution to the photodissociation process. Two timescales obtained from the population dynamics, 26 and 113 fs, are attributed to internal conversion from the second excited La state to the π-σ* states and photodissociation at the π-σ*, respectively, and are in good agreement with timescales obtained from previous experimental studies. Around 80% reaction probability for N-H fission of indole is recorded after 200 fs. This study of photofission of indole is crucial for understanding the photodynamics of similar large molecules.